Being a Woman and an Alevi in Urban Area in the Light of Pseudo-Freedom and Inherent Equality Discussions - Salman, Cemal (Journal of Alevism-Bektashism Studies, 2017)
Studies done about the effects of migration process and urbanization on reshaping gender-related roles and especially on the position of women concluded that migration, on one side, facilitated new chances/opportunities for women while urban area, on the other side, did not directly facilitate an area of freedom for women since socio-economical change did not happen simultaneously with cultural development. These studies also showed that old customs and patriarchal practices are still influential in many aspects of the urban area because of the same reason. According to the writers, as Pessar and Unat, this “binary effect” leads to formation of an area of pseudo-freedom for women.I address on this, the changes of women’s position based on migration and urbanization, in the case of Alevi women and within the context of society-opinion leadership. Some of the recent studies on this subject, which has been neglected both in the literature of migration and in the literature of Alevism, also focus on the discussions which re-produce or criticize “Men and women are inherently equal in Alevism” discourse for urban areas rather than on the effects of the migration on Alevi women. My opinion is that this discourse facilitates a significant area of freedom for women on one side by keeping the emphasis on the equality between man and woman vigorous; however, on the other side, this discourse sets the discussion about gender among the Alevis and more specifically on social position of women aside by constraining this discussion to a cliché discourse.Methodologically, my study is based on literature discussions, and also based on the qualitative research data gotten from my notes, observations and my interviews with Alevi women who are presidents of Alevi organizations which are at different levels from local associations to international federations, whilst carrying out field studies of my dissertation in urban, rural and diasporic areas between 2013-2015, which has been separately derived and not used on dissertation.
Keywords: Migration; Urbanization; Women; Pseudo Freedom; Alevism